Bibliometric Analysis of the Role of Online Marketing on MSME Actors in the Pandemic Period - Laila Tiffany Hasibuan; Andri Soemitra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Economic activity is one of the many significant sectors to affect the level of welfare of a country, including Indonesia. One of the activities included in the economy itself is the activities of MSMEs which have recently begun to be noticed and empowered by the government. This research is a literature study by analyzing several selected literatures in the last 4 years sourced from Google Scholar. The results of this study state that Online Marketing has a significant role as one of the strategies for MSME actors during the Corona Virus Disease-19 pandemic that has hit over the past few years, increasing sales levels, and helping MSME actors to learn technology literacy that is transitioning from system conventional to online systems.